Metformin versus Metformin Plus Statin Effect on Lipid Profile in Type 2 Diabetic Patients - Albarasi, Abeer; Alasbily, Hamza; Elawamy, Hayam; Ibrahim, Arwa; Albarasi, Hamida; Alfituri, Aisha; Alalagy, Sufian; Jabir, Suhir (AlQalam Journal of Medical and Applied Sciences, 2024)
Metformin is commonly used drug for type 2 diabetes and may also impact lipid profiles. Statins are often combined with metformin to manage dyslipidemia, but their comparative efficacy on lipid profiles is not well established. This study aimed to compares the effects of metformin alone versus metformin with statins on lipid profiles and to investigate the impact of different metformin doses on these profiles. A cross-sectional study was conducted at Aljabal Alakdar Diabetic Clinic in East Libya from July to December 2023, involving 200 adults with type 2 diabetes. Participants were divided into Group A (metformin only) and Group B (metformin plus statin). Inclusion criteria were adults aged 18-75 years, on metformin for at least 3 months, with recent lipid profile data, and who provided informed consent. Exclusion criteria were additional lipid-lowering drugs or any medications known to affect lipid profiles, type 1 diabetes, severe comorbidities, and pregnancy. Data were analyzed using SPSS version 27 with MANOVA, and significance was set at p < 0.005. The mean age was 58.62 years, mean diabetes duration was 11.43 years, with 47.5% males and 52.5% females. Mean HbA1c was 7.98%, mean urea was 36.5 mg/dL, and mean creatinine was 0.95 mg/dL. Lipid profile parameters included mean LDL cholesterol at 89.09 mg/dL, HDL cholesterol at 47.71 mg/dL, total cholesterol at 175.6 mg/dL, and triglycerides at 169.4 mg/dL. The key lipid parameters showed a significant difference (p < 0.000) between groups, with the metformin-only group exhibiting lower LDL, HDL, triglycerides, and total cholesterol compared to the metformin plus statin group. Our study found that metformin alone achieved better lipid control than metformin combined with statins, with a 1g dose showing notable antihyperlipidemic effects. عقار الميتفورمين هو دواء شائع الاستخدام لعلاج مرض السكري من النوع الثاني وقد يؤثر أيضًا على مستويات الدهون في الدم. غالبًا ما يتم الجمع بين ادوية الستاتين و عقار الميتفورمين للتحكم في اضطراب مستويات الدهون في الدم، ولكن فعاليتهما المقارنة على مستويات الدهون غير مثبتة جيدًا. تهدف هذه الدراسة إلى مقارنة تأثيرات عقار الميتفورمين وحده مقابل عقار الميتفورمين مع ادوية الستاتين على مستويات الدهون والتحقيق في تأثير جرعات عقار الميتفورمين المختلفة على هذه المستويات. أجريت دراسة مقطعية في مركز الجبل الأخضر للسكري في شرق ليبيا من يوليو إلى ديسمبر 2023، وشارك فيها 200 بالغ مصاب بداء السكري من النوع الثاني. تم تقسيم المشاركين إلى المجموعة أ (الميتفورمين فقط) والمجموعة ب (الميتفورمين بالإضافة إلى الستاتين). كانت معايير الإدراج هي البالغين الذين تتراوح أعمارهم بين 18 و75 عامًا، والذين يتناولون عقار الميتفورمين لمدة 3 أشهر على الأقل، ولديهم بيانات حديثة لمستويات الدهون في الدم ، والذين قدموا موافقة علي المشاركة. وكانت معايير الاستبعاد هي الأدوية الإضافية الخافضة للدهون ومرض السكري من النوع الأول، والأمراض المصاحبة الشديدة، والحمل. تم جمع البيانات وإدخالها وتحليلها احصائيا. كان متوسط ​​العمر 58.62 عامًا، ومتوسط ​​مدة الإصابة بمرض السكري 11.43 عامًا، مع 47.5٪ من الذكور و52.5٪ من الإناث. كان متوسط معدل السكر التراكمي 7.98%، وكان متوسط ​​اليوريا 36.5 مجم/ديسيلتر، وكان متوسط ​​الكرياتينين 0.95 مجم/ديسيلتر. وتضمنت معايير مستويات الدهون في الدم متوسط ​​كوليسترول البروتين الدهني منخفض الكثافة عند 89.09 مجم/ديسيلتر، وكوليسترول البروتين الدهني مرتفع الكثافة عند 47.71 مجم/ديسيلتر، والكوليسترول الكلي عند 175.6 مجم/ديسيلتر، والدهون الثلاثية عند 169.4 مجم/ديسيلتر. أظهرت معايير الدهون الرئيسية اختلافات كبيرة بين المجموعات، حيث أظهرت المجموعة التي تناولت عقار الميتفورمين فقط انخفاضًا في البروتين الدهني منخفض الكثافة والبروتين الدهني مرتفع الكثافة والدهون الثلاثية والكوليسترول الكلي مقارنة بالمجموعة التي تناولت عقار الميتفورمين بالإضافة إلى ادوية الستاتين. أثرت جرعة 1 جرام من عقار الميتفورمين بشكل ملحوظ على مستويات الدهون في الدم. وجدت دراستنا أن عقار الميتفورمين وحده حقق سيطرة أفضل على الدهون مقارنة بعقار الميتفورمين مع ادوية الستاتين، حيث أظهرت جرعة 1 جرام تأثيرات مضادة لاضطراب مستويات الدهون في الدم